2005
DOI: 10.1016/j.aop.2005.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and phases of flocks

Abstract: We review the past decadeÕs theoretical and experimental studies of flocking: the collective,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
1,072
7
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 940 publications
(1,110 citation statements)
references
References 84 publications
23
1,072
7
8
Order By: Relevance
“…Most of all the previous theoretical studies on polar active matter have reported the emergence of "giant density fluctuations" in polar liquids. Giant density fluctuations were believed to be a robust and generic feature of active polar liquids [46,48]. Although our model includes classical alignment interactions, it also contains additional repulsive and dipolar couplings: among them, the long-range hydrodynamic interactions destroy the giant density fluctuations, as we show below.…”
Section: Density Fluctuationsmentioning
confidence: 84%
See 2 more Smart Citations
“…Most of all the previous theoretical studies on polar active matter have reported the emergence of "giant density fluctuations" in polar liquids. Giant density fluctuations were believed to be a robust and generic feature of active polar liquids [46,48]. Although our model includes classical alignment interactions, it also contains additional repulsive and dipolar couplings: among them, the long-range hydrodynamic interactions destroy the giant density fluctuations, as we show below.…”
Section: Density Fluctuationsmentioning
confidence: 84%
“…Guided by this universal feature, physicists have proposed that solely alignment rules at the individual level could account for the emergence of unidirectional motion at the group level [1][2][3][4] . This hypothesis has been supported by agent-based simulations 1,5,6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviour of self-propelled objects such as bacteria, algae and synthetic Janus particles has become a dynamic field of research, both for the 'swimming' of individual particles (Lauga & Powers 2009) and for the collective behaviour of active suspensions (Toner, Tu & Ramaswamy 2005). Owing to the particles' self-motion, active matter can spontaneously phase-separate into dense and dilute regions (Cates et al 2010;Fily & Marchetti 2012;Buttinoni et al 2013;Palacci et al 2013;Stenhammar et al 2013Stenhammar et al , 2014Takatori, Yan & Brady 2014;Wysocki, Winkler & Gompper 2014;Yang, Manning & Marchetti 2014;Takatori & Brady 2015) and can move collectively under an orienting field .…”
Section: Introductionmentioning
confidence: 99%
“…A constant term is not considered in the above expression since the constant contribution can be absorbed by c, the rate of internal dissipation in the energy balance (2). The effects of coefficients a i have been discussed systematically in the previous work [12].…”
Section: Model For Kinesin Motor On Microtubulementioning
confidence: 99%